2022
DOI: 10.1136/bmjopen-2021-059321
|View full text |Cite
|
Sign up to set email alerts
|

Severe COVID-19 anxiety among adults in the UK: protocol for a cohort study and nested feasibility trial of modified cognitive–behavioural therapy for health anxiety

Abstract: Introduction Some people are so anxious about COVID-19 that it impairs their functioning. However, little is known about the course of severe COVID-19 anxiety or what can be done to help people who experience it. Methods and analysis Cohort study with a nested feasibility trial with follow-up at 3 and 6 months. We recruited 306 people who were aged 18 and over, lived in the UK and had severe COVID-19 anxiety (indicated by a score of 9 or more on the Coronavirus Anxiety Scale (CAS)). To take part in the neste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…This two-step analytic cross-sectional study uses data collected at baseline from Imperial College London’s COVID-19 Anxiety Project (CAP), a longitudinal study of people with severe COVID anxiety, a full description of which has been published elsewhere [ 35 ]. This article was written in line with STROBE guidelines for cross-sectional studies [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…This two-step analytic cross-sectional study uses data collected at baseline from Imperial College London’s COVID-19 Anxiety Project (CAP), a longitudinal study of people with severe COVID anxiety, a full description of which has been published elsewhere [ 35 ]. This article was written in line with STROBE guidelines for cross-sectional studies [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…21 participants were excluded from these analyses as they received a course of adapted CBT for Health Anxiety as part of the nested feasibility trial which we anticipated would influence the natural trajectory of severe COVID anxiety. (21) There were significant rates of mental health conditions in this cohort, and otherwise nationally representative rates of at-risk health conditions. A full description of baseline cohort characteristics has been reported previously.…”
Section: Methodsmentioning
confidence: 67%
“…We previously conducted analysis on this same cohort at the 6-month time-point (22) which identified that older age, higher baseline levels of generalised and health anxiety, and greater reductions in health anxiety and depressive symptoms were significantly associated in multivariable models with greater reductions in COVID anxiety. These findings are again demonstrated one year later at the 18-month follow-up timepoint, however the effect of baseline mental health scores become no longer predictive of the longer-term trajectory of severe COVID anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations